Identification of the Key Factors Affecting the Adoption of Mobile Phone Gaming: A Study in the Context of Bangladesh. (Global Journal of Management and Business Research, 2015)
In recent years the use of mobile phones and smart phones have become more widespread and continue to grow significantly and almost half of the population of the earth now use mobile communications. The mobile telecommunications industry is a key driver of both economic and social development across the globe and it is one of the most transformational industries in the world today, enriching the daily lives of almost half of the world's population and mobile device is becoming part and parcel in our daily life and plays a pivotal role in passing time and recreation device for people specially young generation. This study investigates the identification of the key factors affecting the adoption of mobile phone gaming in the context of Bangladesh.
Keywords: mobile phone gaming; adoption; usefulness; personal attitude; concentration; telecommunication; 3G; smart phones